Study micromixing pada tangki teraduk secara kontinyu - Ali Altway; W Widiyastuti; M Rachimoellah; Sugeng Winardi (Jurnal Teknik Kimia Indonesia, 2004)
The aim of this work is to study the influence of micromixing on product distribution for parallel reaction systems in an agitated tank. The understanding of micromixing is needed besides macromixing to obtain the optimum process. The neutralization reaction of NaH2BO3 and oxidation-reduction reaction between lodide-lodate to generate iodine are selected to perform parallel reaction systems. These reactions were conducted in a flat bottom cylindrical tank 0.2 m in diameter (T) at room temperature (30oC) agitated by six blades fan turbine having diameter (Da)=1/3T and impeller width (W)=1/4T. The impeller clearance was I/3H. The height of liquid in the tank is equal to its diameter (H=T). This tank was operated as continuous reactor type. The inf1uences of impeller speed, residence time and feed position were analyzed. Segregation number and the yield of iodine generation determine the micromixing degree and the performance of reactor respectively. The impeller rotation speed was varied 100-300 rpm. The residence time varied 6.01, 4.005 and 3.005 minutes. The feed position was varied on [r"=r/D, z'=z/H] cylindrical coordinate as follows [1.4, 180o, 0.23], [1.4, 180o, 0.33] and [2.4, 180o, 0.92] which represent bulk swept impeller and near surface regions respectively. By increasing the impeller rotation speed and residence time, the iodine yield decrease.The iodine yield is proportional to segregation number. The segregation number Leads to micromixing degree which higher micromixing degree corresponds to the iodine yield decreasing. The impeller swept position gives the smallest the iodine yield compared to others. Keywords: Micromixing, Yield, Segregasion Number.AbstrakPenelitian ini bertujuan untuk mempelajari pengaruh micromixing pada distribusi produk untuk reaksi paralel dalam sistem tangki teraduk. Pemahaman tentang micromixing dalam suatu sistem diperlukan disamping macromixing untuk mendapatkan proses yang optimum. Pada penelitian ini reaksi paralel ini diwakili oleh reaksi netralisasi NaH2BO3 dan reaksi oksidasi-reduksi Iodide-lodate yang menghasilkan lodin. Reaktor beroperasi kontinyu pada suhu kamar (30oC) berupa tangki silinder berdasar datar berdiameter (T)=0.2 m yang diaduk dengan fan turbin enam blade berdiameter (Da)=1/3T dan lebar impeller (W)=1/4T yang dipasang 1/3H dari dasar. Tinggi cairan sama dengan diameter tangki (H=T). Pengaruh kecepatan putar impeller, waktu tinggal dan posisi umpan dianalisa. Bilangan segregasi dihitung untuk menentukan derajat micromixing dan menghitung yield pembentukan iodin untuk menentukan unjuk kerja reaktor. Kecepatan putar impeller divariasi 100-300 rpm. Waktu tinggal divariasikan 6.01, 4.005 and 3.005 menit. Posisi umpan [r'=r/D, z'=z/H] yang merupakan koordinat silinder divariasikan [1.4, 180o, 0.23], [1.4, 180o, 0.33] and [2.4, 180o, 0.92] yang menyatakan masing-masing daerah bulk bawah, sapuan impeller dan dekat permukaan. Semakin tinggi kecepatan putar impeller dan semakin lama waktu tinggal, yield iodin yang dihasilkan semakin keci1. Yield iodin yang dihasilkan sebanding dengan bilangan segregasi. Bilangan segregasi menunjukkan tingkat micromixing dimana semakin besar tingkat micromixing semakin kecil yield iodin yang dihasilkan. Posisi umpan yang memberikan yield iodin yang terkecil adalah pada daerah sapuan impeller. Kata Kunci: Micromixing, Yield, Bilangan Segregasi.